A strategy for technology development for semi-arid sub-Saharan Africa - Sanders, J.H.; Shapiro, Barry I.; Ramuswamy, S. (International Livestock Research Institute, 1998)
Pessimistic views are often advanced about the future of agricultural development in sub-Saharan Africa, where rapid population and declining food production growth trends have been observed. This has especially been the case with regard to semi-arid Africa where rainfall is low and irregular, and soils fragile and with low fertility. Such views ignore the fact that there have been successful technological break-throughs in the semi-arid region which have resulted in substantial agricultural productivity gains. Successful technology introductions have addressed principal constraints of water availability and soil fertility in the semi-arid region. A strategy for the rapid introduction of inorganic fertilisers, combined with techniques that increase water availability and increased organic fertiliser use, is proposed here for semi-arid Africa.